Konsep Pendidikan Perempuan Perspektif Raden Ajeng Kartini dan Rahma El-Yunusiyah Serta Relevansi dengan Pendidikan Islam Kontemporer - Dellawati, Dellawati; Subandi, Subandi; Wulandari, Heny (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Historical records show that there are female figures who make great contributions to the development of education in Indonesia. In this regard, this study aims to analyze the concept of women's education from the perspectives of Raden Ajeng KArtini and Rahma El- Yunusiyah. The research method used is cici4d qualitative based on library research. The data used are books related to the two figures. Data analysis is done by analyzing the content of the literature that has been reduced according to the needs of the research topic. The results of the study explain that the concept of women's education from the perspective of Raden Ajeng Kartini and Rahma El-Yunusiyah is very relevant to the concept of contemporary Islamic education. Where the concept of women's education that both of them offer has similarities both in terms of its purpose, function and objectives. Which can be briefly formulated that women's education is important so that women get their rights and can carry out their roles both as servants of God, family members and members of society properly. Based on the above conclusions, the author assumes that women's education needs to be improved in Indonesia cici4d. By combining the thoughts of Kartini and Rahma El-Yunusiyah, this recommendation is expected to provide a foundation for the formation of women's education that is holistic, competitive, and in accordance with human values and Islamic teachings.